EDITORIAL: More than closing loops: Community-based circular food systems as pathways for transformation - María Alonso Martínez; Jacob Park; Anna Davies; WarīNkwī Flores; Sarah Rocker; Jim Worstell (Journal of Agriculture, Food Systems, and Community Development)
Introduction